2018
DOI: 10.1103/physrevfluids.3.013906
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and stability analysis of oblique shock-wave/boundary-layer interactions at Mach 5.92

Abstract: We investigate flow instability created by an oblique shock wave impinging on a Mach 5.92 laminar boundary layer at a transitional Reynolds number. The adverse pressure gradient of the oblique shock causes the boundary layer to separate from the wall, resulting in the formation of a recirculation bubble. For sufficiently large oblique shock angles, the recirculation bubble is unstable to three-dimensional perturbations and the flow bifurcates from its original laminar state. We utilize Direct Numerical Simulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 56 publications
(78 reference statements)
10
58
0
Order By: Relevance
“…5.25δ 0 . This finding confirms the existence of a spanwise undulation motion of the reflected shock foot and separated area, the latter being consistent with the findings of Hildebrand et al (2018) and Pasquariello et al (2017) who reported a spanwise modulation of the separated area and specifically its reattachment line.…”
Section: Lasupporting
confidence: 92%
“…5.25δ 0 . This finding confirms the existence of a spanwise undulation motion of the reflected shock foot and separated area, the latter being consistent with the findings of Hildebrand et al (2018) and Pasquariello et al (2017) who reported a spanwise modulation of the separated area and specifically its reattachment line.…”
Section: Lasupporting
confidence: 92%
“…and the perturbed dynamic viscosity is given by µ = (∂μ/∂T )T . We verified the accuracy of this characteristic formulation in Hildebrand et al 7 by comparing our results from GSA to Malik's stability analysis 34 of parallel high-speed boundary layers. Global modes of the linear system (4) take the form…”
Section: Linearized Modelsupporting
confidence: 65%
“…Centrifugal instability contributes to the formation of elongated streamwise structures downstream. 7 Since this oblique shock wave/laminar boundary layer interaction has several competing nonmodal transient growth mechanisms, more calculations and analyses need to be performed in the future. approach for a Mach 5.92 SWBLI with θ = 13 • and β = 0.75 at t = 175.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations